Corporate Governance and Firm Performance During the COVID-19 Pandemic: Evidence from Indonesia - Natalia, Maria; SeTin, SeTin; Witanto, Revaldo Farrel (Universitas Kristen Maranatha, 2024)
Abstract Purpose - This study intends to see how corporate governance impacted firm performance during the COVID-19 pandemic across firms registered on the Indonesia Stock Exchange, except the financial industry. Design/methodology/approach - The period of this study is 2020, where the COVID-19 pandemic occurred. This research refers to research conducted by Khatib & Nour (2021). Their research found that board size has a significant positive impact on firm performance, while board meetings and audit committee meetings have a significant negative effect on firm performance. Findings - This study distinguishes itself from earlier studies by using the ASEAN CG Scorecard as a measurement criteria for corporate governance practices, which is still rarely employed in studies with similar topics. The results showed that corporate governance had an impact on firm performance during the COVID-19 pandemic in 279 firms registered on the Indonesia Stock Exchange. This study is consistent with Sami et al. (2011), Guney et al. (2020), and Khatib & Nour (2021). Research limitations/implications - This study only examines the impact of corporate governance on firm performance during the COVID-19 pandemic while before the pandemic was not examined so that the results cannot be compared. Keywords: ASEAN CG Scorecard, Board Size, Company Performance, and Corporate Governance, COVID-19